1975
DOI: 10.1021/ja00859a008
|View full text |Cite
|
Sign up to set email alerts
|

Quantitative study of solvent effects on Menshutkin reaction between 1,4-diazabicyclo[2.2.2]octane and (2-chloroethyl)benzene, (2-bromoethyl)benzene, and (2-iodoethyl)benzene

Abstract: By kinetic studies and product analysis, we have shown that the reaction between 1,4-diazabicyclo[2.2.2]octane on the one hand and (2-chloroethyl)benzene, (2-bromoethyl)benzene, and (2-iodoethyl)benzene on the other hand are Menshutkin quaternization reactions. By working in pure solvents and making use of the correlation method, the irregular behavior of protic solvents is shown. This is interpreted in terms of specific interactions between the protic solvents on the one hand and the halides on the other. The… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

1976
1976
2014
2014

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(4 citation statements)
references
References 0 publications
0
4
0
Order By: Relevance
“…70 Also, the ratio of second-order rate constants in the reaction of 2-phenylethyl bromide and chloride with 1,4-diazabicyclo[2.2.2]octane are k 2 (RBr)/k 2 (RCl) ) 169 in acetone (dielectric constant 21) and 50 in ethanol (with similar dielectric constant of 25). 71 It is therefore not surprising that the reactivities of 1-PhEtBr and 1-PhEtCl toward pyridine in an acetone-pyridine mixture (nonprotic and of relatively low polarity) are markedly more different than those toward water and methanol (in protic and more polar media). The solvolysis and pyridinolysis studies clearly show that, to preserve the living polymer chains throughout the ATRP of styrene-type monomers in the presence of nucleophilic compounds, alkyl chloride initiators should be used.…”
Section: Resultsmentioning
confidence: 99%
“…70 Also, the ratio of second-order rate constants in the reaction of 2-phenylethyl bromide and chloride with 1,4-diazabicyclo[2.2.2]octane are k 2 (RBr)/k 2 (RCl) ) 169 in acetone (dielectric constant 21) and 50 in ethanol (with similar dielectric constant of 25). 71 It is therefore not surprising that the reactivities of 1-PhEtBr and 1-PhEtCl toward pyridine in an acetone-pyridine mixture (nonprotic and of relatively low polarity) are markedly more different than those toward water and methanol (in protic and more polar media). The solvolysis and pyridinolysis studies clearly show that, to preserve the living polymer chains throughout the ATRP of styrene-type monomers in the presence of nucleophilic compounds, alkyl chloride initiators should be used.…”
Section: Resultsmentioning
confidence: 99%
“…Bond formation and bond cleavage are both slight in the transition state (8) but extensive in the transition state ( 9 ) . The ratio of bond formation and bond cleavage turns out to be almost independent of substituent variation in (5 On the other hand, the ratio of bond formation and bond cleavage is not constant when arenesulfonyl chlorides (7) react with an aniline/3-chloroaniline system, because substituent variation on sulfonyl chlorides influences bond formation and bond cleavage in opposite directions: a methoxy group at position 4 of the arenesulfonyl chloride impedes formation of a negative charge at the sulfur atom, but facilitates the expulsion of the chloride ion. A nitro group on ( 7 ) , however, promotes formation of the N-S bond and impedes cleavage of the S-Cl bond.…”
Section: Limitations Of the Reactivity-selectivity Principlementioning
confidence: 95%
“…Both the addition of bases and the use of other solvents were completely ineffective for this transformation, so either no 4a or a very low yield (Table 1, entries 1-24) was obtained. The inhibitory effect of various solvents on this reaction can be explained on the basis of solvation of the amine, which is quite facile especially in the case of protic solvents, and results in the formation of hydrogen bonds between the amine and the solvent, 14 consequently weakening the nucleophilic character of the amine and leading to a slower reaction rate. 8a,14 Moreover, it was observed that this reaction was susceptible to temperature changes.…”
Section: Resultsmentioning
confidence: 99%